2020
DOI: 10.1039/d0nr01955k
|View full text |Cite
|
Sign up to set email alerts
|

New theoretical insights into high-coordination-number complexes in actinides-centered borane

Abstract: The coordination number of a given element affects its behavior, and consequently, there is great interest in understanding the related chemistry, which could greatly promote the extension and development of new materials, but remains challenging.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…16 According to their work, 18 He atoms can be accommodated in the first coordination shell, in a highly symmetrical D 4d structure, the increase in CN from our work potentially being due to omission of basis set superposition error (BSSE) in our CCSD(T) calculations. Although CN higher than 18 has recently been reported for M(H 2 ) 12 n+ (M = Ac, Th, Pa, U, La, n = 3, 4) 17 and An(BH) 24 (An = Th-Cm), 18 genuine CNs of 24 are debatable given the strong H-H interaction in M(H 2 ) 12 n+ and lack of direct evidence for true 24 M-B bonds in An(BH) 24 . High coordination number is also observed in metal cluster-based compounds.…”
Section: Introductionmentioning
confidence: 79%
“…16 According to their work, 18 He atoms can be accommodated in the first coordination shell, in a highly symmetrical D 4d structure, the increase in CN from our work potentially being due to omission of basis set superposition error (BSSE) in our CCSD(T) calculations. Although CN higher than 18 has recently been reported for M(H 2 ) 12 n+ (M = Ac, Th, Pa, U, La, n = 3, 4) 17 and An(BH) 24 (An = Th-Cm), 18 genuine CNs of 24 are debatable given the strong H-H interaction in M(H 2 ) 12 n+ and lack of direct evidence for true 24 M-B bonds in An(BH) 24 . High coordination number is also observed in metal cluster-based compounds.…”
Section: Introductionmentioning
confidence: 79%
“…31 Energy decomposition analyses (EDA) 32 were carried out using the combined Extended Transition State (ETS) with the Natural Orbitals for Chemical Valence (NOCV) [33][34] theory to assess different orbital contributions to the total bonding energies. The population partitioning schemes of Mulliken 35 were used to determine the atomic charges of the atoms in these species. This procedure has shown reasonable results to support and explain experiments in the study of geometrical structure and electronic structure of actinide clusters.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In addition, global searches revealed that U@B 24 has a half-cage structure. 35 This raises the question, if other actinide metal atoms are doped into the slightly larger boron clusters B 24 , which structure is more stable, tubular, half-cage, or cage-like? Is it possible to form larger metal-centered tubular boron clusters?…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other metal atoms, doping with actinides can improve the stability of boron clusters, and these clusters exhibit a variety of geometrical structures. For example, the half sandwich structures AnB 12 (An = Th to Cm), the actinide endohedral borospherenes An@B n (An = U and Th; n = 36, 38, and 40), , the chiral actinide endohedral borospherenes (Ac@B 39 , [Ac@B 39 ] 2+ , and Th@B 39 , [Th@B 39 ] 3+ ), and the actinide-centered borane An­(BH) 24 (An = Th to Cm) have been demonstrated by theoretical calculations. Very recently, we reported a series of actinide metal atom (U, Np, and Pu)-doped B 20 boron clusters An@B 20 .…”
Section: Introductionmentioning
confidence: 99%